Antimicrobial peptides: a new class of antimalarial drugs? - Vale, Nuno; Aguiar, Luísa; Gomes, Paula (Frontiers in Pharmacology, 2014)
A range of antimicrobial peptides (AMP) exhibit activity on malaria parasites, Plasmodium spp, in their blood or mosquito stages, or both. These peptides include a diverse array of both natural and synthetic molecules varying greatly in size, charge, hydrophobicity and secondary structure features. Along with an overview of relevant literature reports regarding AMP that display antiplasmodial activity, this review makes a few considerations about those molecules as a potential new class of antimalarial drugs.